The Effect of Diagnostic Assessment on Mathematics Learning Outcomes Using the Problem Based Learning Model in Grade VII Students of Maubeli State Junior High School - Reli Maria Aurelia Luti (MATH-EDU: Jurnal Ilmu Pendidikan Matematika, 2025)
This study aims to determine the influence of non-cognitive diagnostic assessments on mathematics learning outcomes using the Problem Based Learning (PBL) learning model in grade VII students of Maubeli State Junior High School. This study uses experimental research with a quantitative approach, namely quasi-experimental with a Pretest-Posttest Non-Equivalent Control Group Design research design. The research population is grade VII students. Sampling uses probability sampling techniques with purposive sampling techniques. The sample in this study is class VIIB and class VIIC. Data collection techniques with questionnaires and tests. The results of the study showed that: 1) the average learning outcomes of students in the experimental class reached the KKM. 2) The average learning outcomes of the experimental class were different from thecontrol class. 3) the Independent variable has a significant effect simultaneously (together) on the Depeneden variable.